Mercury in Ten Storm-Petrel Populations from the Antarctic to the Subtropics - Quillfeldt, Petra; Bedolla-Guzmán, Yuliana; Libertelli, Marcela M.; Cherel, Yves; Massaro, Melanie; Bustamante, Paco; Justus Liebig University Giessen (My University, 2023)
The oceans become increasingly contaminated as a result of global industrial production and consumer behaviour, and this affects wildlife in areas far removed from sources of pollution. Migratory seabirds such as storm-petrels may forage in areas with different contaminant levels throughout the annual cycle and may show a carry-over of mercury from the winter quarters to the breeding sites. In this study, we compared mercury levels among seven species of storm-petrels breeding on the Antarctic South Shetlands and subantarctic Kerguelen Islands, in temperate waters of the Chatham Islands, New Zealand, and in temperate waters of the Pacific off Mexico. We tested for differences in the level of contamination associated with breeding and inter-breeding distribution and trophic position. We collected inert body feathers and metabolically active blood samples in ten colonies, reflecting long-term (feathers) and short-term (blood) exposures during different periods ranging from early non-breeding (moult) to late breeding. Feathers represent mercury accumulated over the annual cycle between two successive moults. Mercury concentrations in feathers ranged over more than an order of magnitude among species, being lowest in subantarctic Grey-backed Storm-petrels (0.5 μg g−1 dw) and highest in subtropical Leach’s Storm-petrels (7.6 μg g−1 dw, i.e. posing a moderate toxicological risk). Among Antarctic Storm-petrels, Black-bellied Storm-petrels had threefold higher values than Wilson’s Storm-petrels, and in both species, birds from the South Shetlands (Antarctica) had threefold higher values than birds from Kerguelen (subantarctic Indian Ocean). Blood represents mercury taken up over several weeks, and showed similar trends, being lowest in Grey-backed Storm-petrels from Kerguelen (0.5 μg g−1 dw) and highest in Leach’s Storm-petrels (3.6 μg g−1 dw). Among Antarctic storm-petrels, species differences in the blood samples were similar to those in feathers, but site differences were less consistent. Over the breeding season, mercury decreased in blood samples of Antarctic Wilson’s Storm-petrels, but did not change in Wilson’s Storm-petrels from Kerguelen or in Antarctic Black-bellied Storm-petrels. In summary, we found that mercury concentrations in storm-petrels varied due to the distribution of species and differences in prey choice. Depending on prey choices, Antarctic storm-petrels can have similar mercury concentrations as temperate species. The lowest contamination was observed in subantarctic species and populations. The study shows how seabirds, which accumulate dietary pollutants in their tissues in the breeding and non-breeding seasons, can be used to survey marine pollution. Storm-petrels with their wide distributions and relatively low trophic levels may be especially useful, but more detailed knowledge on their prey choice and distributions is needed.
Keywords: ddc:570; ddc:590